An Engineered E. coli Strain for Direct in Vivo Fluorination. (3rd March 2020) - Markakis, Konstantinos; Lowe, Phillip T.; Davison‐Gates, Liam; O'Hagan, David; Rosser, Susan J.; Elfick, Alistair
Abstract: Selectively fluorinated compounds are found frequently in pharmaceutical and agrochemical products where currently 25–30 % of optimised compounds emerge from development containing at least one fluorine atom. There are many methods for the site‐specific introduction of fluorine, but all are chemical and they often use environmentally challenging reagents. Biochemical processes for C−F bond formation are attractive, but they are extremely rare. In this work, the fluorinase enzyme, originally identified from the actinomycete bacterium Streptomyces cattleya, is engineered into Escherichia coli in such a manner that the organism is able to produce 5′‐fluorodeoxyadenosine (5′‐FDA) from S ‐adenosyl‐l ‐methionine (SAM) and fluoride in live E. coli cells. Success required the introduction of a SAM transporter and deletion of the endogenous fluoride efflux capacity in order to generate an E. coli host that has the potential for future engineering of more elaborate fluorometabolites. Abstract : Fluorinated organic molecules are of great value both for agriculture and medicine. However, fluorine chemistry is expensive and harmful to the environment. Natural products are at a premium and are only produced by a handful of organisms. For the first time, an engineered E. coli is presented with the capacity to produce a naturally occurring fluorinated molecule.